2007
DOI: 10.1021/ci700160t
|View full text |Cite
|
Sign up to set email alerts
|

New Serotonin 5-HT6Ligands from Common Feature Pharmacophore Hypotheses

Abstract: Serotonin 5-HT6 receptor antagonists are thought to play an important role in the treatment of psychiatry, Alzheimer's disease, and probably obesity. To find novel and potent 5-HT6 antagonists and to provide a new idea for drug design, we used a ligand-based pharmacophore to perform the virtual screening of a commercially available database. A three-dimensional common feature pharmacophore model was developed by using the HipHop program provided in Catalyst software and was used as a query for screening the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…22 The commonly recognized pharmacophore of the 5-HT 6 R antagonists consists of four key fragments: basic nitrogen atom (PI), hydrophobic core (H), aromatic ring(s) (Ar) and dual acceptor of hydrogen bonds (HBA). [23][24][25][26][27][28] In the pharmacophore model of the 5-HT 6 R antagonists, the sulfonyl fragment is usually considered as the strong hydrogen bond acceptor. [23][24][25]27,28 Based on docking study, it is postulated that it interacts with N6.55 and S5.…”
Section: 16-21mentioning
confidence: 99%
See 1 more Smart Citation
“…22 The commonly recognized pharmacophore of the 5-HT 6 R antagonists consists of four key fragments: basic nitrogen atom (PI), hydrophobic core (H), aromatic ring(s) (Ar) and dual acceptor of hydrogen bonds (HBA). [23][24][25][26][27][28] In the pharmacophore model of the 5-HT 6 R antagonists, the sulfonyl fragment is usually considered as the strong hydrogen bond acceptor. [23][24][25]27,28 Based on docking study, it is postulated that it interacts with N6.55 and S5.…”
Section: 16-21mentioning
confidence: 99%
“…[23][24][25][26][27][28] In the pharmacophore model of the 5-HT 6 R antagonists, the sulfonyl fragment is usually considered as the strong hydrogen bond acceptor. [23][24][25]27,28 Based on docking study, it is postulated that it interacts with N6.55 and S5. 43 forming O-H/O and N-H/O bonds, 23,27,28 respectively.…”
Section: 16-21mentioning
confidence: 99%
“…For pharmacophore generation, three to five inhibitors were carefully selected from each group considering activity, selectivity, and structural rigidity (Kim et al, 2008a structures were reported in the original literature, only one representative compound (usually the most potent one) from each structural class was selected. Structural redundancy is not necessary for the generation of common-feature pharmacophore models.…”
Section: Pharmacophore Generationmentioning
confidence: 99%
“…Since then a lot of reports have been published regarding variations in N,N-dimethyl amino alkyl side chain on and around the indole nucleus and their affinity 21,32,33 ( Figure 2). Numerous selective antagonists of 5-HT 6 receptors have been disclosed during the last decade [34][35][36][37][38][39][40][41][42] and a pharmacophore model for this type of receptor antagonists has been developed based on known structurally diverse 5-HT 6 receptor antagonists [43][44][45][46][47][48][49] . In general, the model entails the positive ionizable atom (usually a secondary or tertiary amino group), a hydrogen bond acceptor group (usually a sulfone or sulfonamide group), a hydrophobic site (HYD) and -electron donor aromatic or heterocyclic ring (AR).…”
Section: Introductionmentioning
confidence: 99%